PTU-153 The Timing Of Oncogenic Events In The Evolution Of The Oesophageal Adenocarcinoma Genome And Implications For Clinical Diagnostics. (9th June 2014) - Weaver, J; Ross-Innes, C; Shannon, N; Lynch, A; Murtaza, M; Forshew, T; Dunning, M; Underwood, T; Hardwick, R; Eldridge, M; Edwards, P; Rosenfeld, N; et al.
Abstract : Introduction: A series of clonal expansions are thought to underlie the progression of Barrett's oesophagus (BE) to oesophageal adenocarcinoma (OAC). Each expansion carries with it somatic driver mutation (s) fixing it within a larger population and therefore increasing the likelihood of acquiring a second mutation. However, the precise order in which somatic variants occur remains unknown. Methods: We performed whole genome sequencing in 25 cases of OAC and 3 matched cases of BE. Findings were validated in a larger cohort of OACs (n = 90), metaplastic never-dysplastic BE (NDBE, n = 66 with a median follow-up of 58 months) and high-grade dysplasia (n = 43) using amplicon resequencing. Mutational signatures and gene-centric somatic mutations were determined using an in-house pipeline incorporating standard statistical methods and the publically available EMu pipeline. Results: There were 7 distinct mutational signatures present in both early (BE) and late disease (OAC). Fifteen genes were determined to be potential novel drivers of OAC development. Surprisingly in 53% of NDBE tissue samples we identified clonal expansion of cells (>10% mutant fraction) harbouring mutations in one or more of 13/15 of these putative driver genes. No difference in the frequency of mutation of these genes was observed between any of the disease stages studied. TP53 mutations clearly delineate between HGD/OAC and benign NDBE (p < 0.001). Whilst SMAD4 mutations are only observed in OAC (p < 0.001) demonstrating for the first time a clear genetic difference between the two. Conclusion: Mutagenic processes active in OAC are also active in the earliest stages of BE. Recurrent driver mutations identified in cancer may be acquired very early in the disease and may provide little or no progression advantage. Molecular diagnostic approaches must account for this. Disclosure of Interest: None Declared.